2020
DOI: 10.1021/acs.jpclett.0c01048
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Carrier Trapping Dynamics in Bismuth-Doped Thin Films of MAPbBr3 Perovskite

Abstract: Successful chemical doping of metal halide perovskites with small amounts of heterovalent metals has attracted recent research attention because of its potential to improve long-term material stability and tune absorption spectra. However, some additives have been observed to impact negatively on optoelectronic properties, highlighting the importance of understanding charge-carrier behavior in doped metal halide perovskites. Here, we present an investigation of charge-carrier trapping and conduction in films o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 41 publications
9
60
0
2
Order By: Relevance
“…Given the long lifetimes of trapped carriers in lead halide perovskite semiconductors, 47 the shorter time period between photoexcitation pulses results in trap filling and population build-up. We investigate the influence of this higher repetition rate by employing a model in which the electron and hole first-order decay rates can vary, as previously implemented, 48 whilst also including the effect of diffusion to account for the rapid early time decay, seen in previous studies. 49 (More details of the model are provided in the ESI.…”
Section: Energy and Environmental Science Papermentioning
confidence: 99%
“…Given the long lifetimes of trapped carriers in lead halide perovskite semiconductors, 47 the shorter time period between photoexcitation pulses results in trap filling and population build-up. We investigate the influence of this higher repetition rate by employing a model in which the electron and hole first-order decay rates can vary, as previously implemented, 48 whilst also including the effect of diffusion to account for the rapid early time decay, seen in previous studies. 49 (More details of the model are provided in the ESI.…”
Section: Energy and Environmental Science Papermentioning
confidence: 99%
“…MHPSCs. Among the 16 types of metal bromide investigated, bismuth bromide [31][32][33][34][35][36] (BiBr3) and silver bromide 37 (AgBr) are considered the most effective donors and acceptors, respectively, due to the high thermally induced diffusion current.…”
Section: Resultsmentioning
confidence: 99%
“…They also observed a darkening of the crystal color and proposed that this is due to band gap narrowing [19] . However, subsequent investigations showed that the color change is due to the introduction of defects [20–22] . The effect of bismuth doping on the photovoltaic performance of lead iodide perovskites is a point of ongoing research: Troshin and Tress found that Bi doping is highly detrimental to the power conversion efficiency of (CH 3 NH 3 )PbI 3 solar cells [23, 24] .…”
Section: Figurementioning
confidence: 99%